14.8k views
3 votes
please answer the question on the screenshot below, also please explain to me how you got your answer.

please answer the question on the screenshot below, also please explain to me how-example-1
please answer the question on the screenshot below, also please explain to me how-example-1
please answer the question on the screenshot below, also please explain to me how-example-2
please answer the question on the screenshot below, also please explain to me how-example-3
User Pranit
by
4.2k points

1 Answer

6 votes

QUESTION 1

The given functions are;


f(x)=5x^2-2x and
g(x)=5x^2+x-4


(f+g)(x)=f(x)+g(x)


(f+g)(x)=5x^2-2x+3x^2+x-4

We regroup like terms to obtain;


(f+g)(x)=5x^2+3x^2-2x+x-4

This simplifies to;


(f+g)(x)=8x^2-x-4

The correct answer is A.

QUESTION 2

The given functions are;


f(x)=3x^2+5 and
g(x)=x-2.


(fg)(x)=(f(x))(g(x))

This implies that;


(fg)(x)=(3x^2+5)(x-2)


\Rightarrow (fg)(x)=3x^3-6x^2+5x-10

The correct answer is B.

QUESTION 3

The given functions are


f(x)=3x^2+10x-8 and
g(x)=3x^2-2x.


((f)/(g))(x)=(f(x))/(g(x))


((f)/(g))(x)=(3x^2+10x-8)/(3x^2-2x),x\\e0,(2)/(3)

We factor to obtain;


((f)/(g))(x)=((x+4)(3x-2))/(x(3x-2)),x\\e0,(2)/(3)

We cancel the common factors to obtain;


((f)/(g))(x)=(x+4)/(x),x\\e0,(2)/(3)

The correct answer is A.

User Akuta
by
5.2k points